CALDERA-FORMING PROCESSES AND THE ORIGIN OF SUBMARINE VOLCANOGENIC MASSIVE SULFIDE DEPOSITS - Stix J.; Kennedy B.; Hannington M.; Gibson H. (My University, 2003)
Certain volcanogenic massive sulfide (VMS) ore deposits form in submarine calderas. This association is well known, but the link between caldera formation and the origins of the deposits remains poorly understood. Here we show that the size and location of a VMS deposit within a submarine caldera may be determined by how and when the caldera formed. These spatial-temporal conditions control development of the hydrothermal system associated with the VMS deposit. We propose that caldera opening along outward-dipping faults promotes magma degassing, seawater influx, and high-temperature leaching, resulting in a metal-rich hydrothermal fluid. These outward-dipping faults are considered to provide critical pathways for ore-forming fluids responsible for some caldera-hosted VMS deposits and may also be fundamentally important for the formation of many other caldera-hosted ore deposit types.
Keywords: calderas; volcanogenic massive sulﬁde deposits; ﬂuids; subsidence